Improving a procedure for estimating the suitability of raw material mixtures for molding articles by a semi-dry pressing method based on the analysis of compression curves - Savchenko, Oleksandr; Krot, Oleksandr; Butskyi, Vyacheslav; Krot, Olga; Butska, Larisa (Eastern-European Journal of Enterprise Technologies, 2020)
This paper has proposed a simplified procedure for the rapid assessment of the suitability of small-scale articles made from various raw mixtures (hereafter referred to as mixtures) for semi-dry pressing (SP) at molding presses, which could employ fillers composed of slag, ash, dust, and other industrial waste, whose properties are heterogeneous. The procedure is based on an assessment of the degree of negative impact on the quality indicators of articles due to the error of their density Dρ≥±2.5 %, associated with the imperfection of bulk dosing devices that the SP molding presses are equipped with. It has been established that the mixtures can be graded on the basis of the steepness of a compression curve (CC) ‒ the dependence qi=f(ρi), where qi and (ρi) are the current values of pressure (in MPa) and density of the mixture array (in g/cm3). A criterion applied to define the mixture’s suitability to SP is a multiplier b (in cm3/g) included in the dependence. It is shown that the mixture of type I (at b≤8) is suitable for SP at the multi-cavity molding presses. The mixture of type III (at b>12) is problematic; its composition must be adjusted to re-determine b. The mixture of type II (at b=8...12) requires additional research, proposed to be carried out in two stages. The first stage implies a low-cost determination of the dependence of the strength of SP samples on pressure σ=f(q) and testing the minimum strength σmin, as well as for the criteria of steepness K and permissible pressure qу. The ranges of K and qу have been determined, in which a more laborious second stage is needed to check for the absence of an «overpressing» defect. If all stages of the tests are successful, the mixture belongs to type I; if not ‒ to type III. Techniques to improve the suitability of the mixtures to SP have been considered. A promising technique has proven to be the treatment of the mixture in a high-speed roller-type activator, which simultaneously reduces both the CC steepness of the activated mixture and the required pressure of pressing. The study results could expand the application scope of anthropogenic products by utilizing them in the mixtures for SP